A malaria vaccine protects Aotus monkeys against virulent Plasmodium falciparum infection - Prakash Srinivasan (Nature Portfolio, 2017)
Malaria: Inhibiting parasite invasion of red blood cells A vaccine targeting a protein complex that allows malaria-causing parasite to enter red blood cells has been produced. Malaria caused by the parasite Plasmodium falciparum is an oft-deadly infectious disease without an effective vaccine. A team of researchers at the National Institutes of Health led by Prakash Srinivasan, currently at the Johns Hopkins Malaria Research Institute, United States, demonstrated the efficacy of a vaccine candidate that works by priming a host’s immune system to a parasitic protein complex required to form a junction with red blood cells, allowing entry and proliferation of the pathogen. The group’s vaccine conferred more effective protection in monkeys than prior candidates that targeted only one component of the parasitic protein complex. This research warrants a closer look into how this candidate, and others targeting the protein complex, can be used to prevent malaria in humans.